Magnetic Domain Structure in Ferromagnetic Kagome Metal DyMn6Sn6 - Chen, Zhaohui; Li, Miao; Liu, Caixing; Ma, Zongwei; Han, Yuyan; Gao, Jianhua; Wei, Wensen; Sheng, Zhigao; Du, Haifeng (Frontiers in Physics, 2021)
Two types of magnetic domains, i.e., type-I domain belt domain and type-II domain new stripe domain are observed in a kagome metal DyMn6Sn6 by microscopic magneto-optic Kerr imaging technique. From 255 K to 235 K, the spin reorientation is observed directly in DyMn6Sn6. We analyze the structure of two types of domains through brightness distribution of the images. The type-II domain exists from 235 K to 160 K by zero field cooling (ZFC). At the same time, type-I domain and type-II domain coexist and transform into each other with the variation of temperature. Type-II domains can easily transform into type-I domains when the temperature and magnetic field changes, and this process is irreversible. These results demonstrate that the type-I domain is more stable than the type-II domain. The phase diagram of magnetic domains in DyMn6Sn6 is obtained.